Potential role of the skin and gut microbiota in premenarchal vulvar lichen sclerosus: A pilot case-control study. - Suhana Chattopadhyay; Justin D Arnold; Leena Malayil; Lauren Hittle; Emmanuel F Mongodin; Kalyani S Marathe; Veronica Gomez-Lobo; Amy R Sapkota (PLoS ONE)
The etiology of vulvar lichen sclerosus (LS) remains unclear; however, alterations in cutaneous and gut microbiota may be contributing to the pathogenesis of this inflammatory condition. To explore this hypothesis, we conducted a pilot case-control study, obtaining dermal swab and stool samples from prepubertal girls with vulvar LS (n = 5), girls with nonspecific vulvovaginitis (n = 5), and healthy controls (n = 3). Samples (n = 56) were subjected to total DNA extractions. Resulting DNA was purified, subjected to PCR (targeting the V3V4 region of the 16S rRNA gene), sequenced, and analyzed using QIIME, MetagenomeSeq, and DESeq2 software packages. Our findings showed that there were significant differences in the cutaneous and gut microbiotas of girls with LS compared to controls. On the skin, girls with LS had a statistically significantly higher relative abundance of Porphyromonas spp., Parvimonas spp., Peptoniphilus spp., Prevotella spp., Dialister spp., and Peptostreptococcus spp., but a lower relative abundance of Cornyebacterium compared to the control group. In the gut samples, girls with LS had a significantly higher relative abundance of Dialister spp., Clostridiales spp., Paraprevotella spp., Escherichia coli, Bifidobacterium adolescentis, and Akkermansia muciniphila, and a lower relative abundance of Roseburia faecis and Ruminococcus bromii compared to controls. These results suggest a potential association between cutaneous and gut dysbiosis and pediatric vulvar LS. Future studies involving larger samples sizes are warranted to further evaluate this association.